Development of energy storage system scheduling algorithm for simultaneous self-consumption and demand response program participation in South Korea - Lee, Wonjun; Kang, Byung O; Jung, Jaesung (Energy (Oxford), 2018)
This paper presents an Energy Storage System (ESS) scheduling algorithm for the simultaneous self-consumption and Demand Response (DR) program participation in South Korea. To do this, two ESS scheduling algorithms are developed to participate in the DR program in South Korea. The first algorithm is designed to maximize the customer's profit using energy arbitrage, after which the remaining ESS capacity is used to participate in the DR program. The second algorithm is designed to maintain its self-consumption at a minimum so that the ESS can participate in the DR program as much as possible. In addition, both algorithms have the same objectives of minimizing the peak demand in order to reduce the contract power as well as to minimize the charge/discharge cycles in order to lengthen the life of ESS. The developed algorithms are validated using the actual industrial load profiles with ESS. Furthermore, the economic analysis is performed when ESS that applies two different algorithms participates in the DR program. The simulation results indicate that the proposed algorithm prioritizing the self-consumption shows a relatively higher profit than that obtained by prioritizing the DR participation owing to uncompetitive compensation of the current South Korea DR program. •ESS algorithms are developed for both self-consumption and DR participation.•The 1st algorithm is designed to maximize the profit from self-consumption.•The 2nd algorithm is designed to maximize the profit from DR program participation.•The operational strategy of ESS to participate in DR program is proposed.•The economic analysis is performed to verify the proposed algorithms.